HIF-1α-induced RIT1 promotes liver cancer growth and metastasis and its deficiency increases sensitivity to sorafenib. (28th September 2019) - Song, Zhen; Liu, Tengfei; Chen, Jing; Ge, Chao; Zhao, Fangyu; Zhu, Miaoxin; Chen, Taoyang; Cui, Ying; Tian, Hua; Yao, Ming; Li, Jinjun; Li, Hong
Abstract: Ras-like-without-CAAX-1 (RIT1) belongs to the RAS superfamily of small GTPases, which plays critical roles in tumor progression. However, little is known about the roles of RIT1 in hepatocellular carcinoma (HCC). Here we found that RIT1 expression was positively associated with the presence of intrahepatic metastasis and the histological grade of HCC and higher RIT1 expression indicated shorter overall survival in HCC patients. In vitro and in vivo studies revealed that RIT1 functioned as an oncogene, as overexpression of RIT1 enhanced HCC cell proliferation and aggressive behavior, whereas silencing RIT1 expression repressed the malignant behaviors. Furthermore, RIT1 deficiency increased drug sensitivity to sorafenib treatment. We further demonstrated that hypoxia-inducible factor 1α (HIF-1α) directly transcriptionally upregulated RIT1, and its stableness was positively correlated with RIT1 expression in HCC tissues. Knockdown of RIT1 attenuated the invasion and migration induced by hypoxia. Collectively, our data highlight the significance of HIF-1α/RIT1 axis in driving HCC progression and sorafenib resistance. Highlights: High expression of RIT1 in HCC tissues is associated with poor prognosis. RIT1 promotes the growth and metastasis of HCC both in vitro and in vivo. RIT1 deficiency confers sensitivity to sorafenib in HCC cell lines. HIF-1α transcriptionally upregulates RIT1 and positively correlates with RIT1 expression in HCC tissue.